ISU-ISU PENGELOLAAN LINGKUNGAN PADA HOTEL BERBINTANG DI BALI - Jaya Pramono (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2016)
Aim of this studyis to identify environmental management issues at starred hotels in Bali. Respondent of thisstudy was 126 hotel manager. The data obtained through questionnaire which was analyzed by descriptivestatistic. The findings show that environmental management issues take an important place to the hotelmanagement and emerge as bases for hotel manager of starred hotels in Bali for carrrying out environmentalmanagement. Out of seven issues analyzed in this study, three of them emerge as important issues i.e. pressurefrom travel agent, pressure from customer and tourist, and cimate change. There is a significant differenceamong one, two, and three starred hotels and four and five starred hotels related to the significance of thoseissues. For manager of one, two, and three starred hotels, those issues are in “important” category, whereasfor four and five starred hotels, they are in “very important” categories which push them to do management ofenvironment.